THE USE OF ICT TO IMPROVE TEACHERSâ SKILL IN LANGUAGE LEARNING IN THE CLASSROOM - Rahman, O. Suzana (Perspective Jurnal Pendidikan Bahasa Inggris, 2013)
T he utili zation of informa tion and co mmuni cati on T ec hnol ogy (IC T ) in lan gua ge learni ng has be en a n import ant an d inte restin g topi c both a mong st ude nts an d a lso tea che rs. T h er e ar e s ome sug gesti ons abo ut w hat t o pr epar e a nd w hat a ctiviti es t h at can b e c ondu ct ed b y teac her s in th e cla ssroom , es pe ciall y f or tea chin g -l ear ning of English l angu ag e th at can be appli ed f o r all subj e ct. T h e us e of IC T w ill not o n ly impro ve t ea ch er âs s ki ll, but it w ill als o ma ke t ea ch ers mor e cr eati ve i n pr epari ng t he mate rial th at w ill be t ransf err ed to the stud ents. Keywords : ICT, language learning,